Changes in the Shape and Volume of Subcortical Structures in Patients With End-Stage Renal Disease - Gu, Wen; He, Ronghua; Su, Hang; Ren, Zhuanqin; Zhang, Lei; Yuan, Huijie; Zhang, Ming; Ma, Shaohui (Frontiers in Human Neuroscience, 2021)
Introduction: End-stage renal disease (ESRD) typically causes changes in brain structure, and patients with ESRD often experience cognitive and sleep disorders. We aimed to assess the changes in the subcortical structure of ESRD patients and how they are associated with cognitive and sleep disorders. Methods: We recruited 36 adult patients on maintenance hemodialysis and 35 age- and gender-matched control individuals. All participants underwent neuropsychological examination, Laboratory blood tests and 3T magnetic resonance imaging (MRI) to acquire T1 anatomical images. We used volumetric and vertex-wise shape analysis approaches to investigate the volumes of 14 subcortical structural (e.g., bilateral accumbens, amygdala, hippocampus, caudate nucleus, globus pallidus, putamen and thalamus) abnormalities in the two groups. Partial correlations and shape correlations analyses were performed to identify associations between subcortical structure, cognition, and sleep quality in ESRD patients. Results: The volumetric analysis showed that compared with the healthy control group, ESRD patients had less bilateral thalamus (left: F = 31.479, p < 0.001; right: F = 22.820, p < 0.001), bilateral accumbens (left: F = 15.321, p < 0.001; right: F = 13.148, p = 0.001) and right amygdala (F = 9.924, p = 0.002) volumes after Bonferroni correction. In the vertex-wise shape analysis, ESRD patients had abnormal regional surface atrophy in the bilateral thalamus, right accumbens, left putamen, and bilateral caudate. Moreover, the Montreal Cognitive Assessment (MoCA) score was associated with volume reducing in the bilateral thalamus (left: Spearman ρ = 0.427, p = 0.009; right: ρ = 0.319, p = 0.018;), and the Pittsburgh Sleep Quality Index (PSQI) score was associated with volume reduction of the bilateral accumbens (left: ρ = −0.546, p = 0.001; right: ρ = −0.544, p = 0.001). In vertex-wise shape analysis correlations, there was a positive significant correlation between regional shape deformation on the bilateral thalamus and MoCA score in patients with ESRD. Conclusion: Our study suggested that patients with ESRD have subcortical structural atrophy, which is related to impaired cognitive performance and sleep disturbances. These findings may help to further understand the underlying neural mechanisms of brain changes in ESRD patients.